PLATELET COUNT AND MEAN PLATELET VALUE OF RABBIT IMPLANTED BALI CATTLE BONE GRAFT - Purbantoro, Steven Dwi; Wirata, I Wayan; Putra, Komang Darma Yudha (Buletin Veteriner Udayana, 2022)
Platelets play an important role in fracture healing. However, its role is still underappreciated. Therefore, this study investigated the values of mean platelet volume (MPV) and platelet count (PC) as the parameters in fracture healing. This study used 10 male local rabbits which were divided into 2 groups randomly, KI (control group) and KII (treatment group). Each femur of both groups was drilled a hole with a diameter of 5 mm, where KI without any substitutes and KII was implanted by demineralized bali cattle bone graft. Each animal was evaluated by collecting its blood from the central auricular vein into an EDTA tube at 24 hours, week 2, 4, and 6 postoperative determining the values of MPV and PC. Results show that treatment shows no differences to MPV and PC, yet time observation does. Overall, MPV and PC were increased in number during observation and are correlated positively.